From research to program design: use of formative research in Haiti to develop a behavior change communication program to prevent malnutrition - Menon, Purnima; Ruel, Marie T.; Loechl, Cornelia U.; Pelto, Gretel H. (SAGE Publications, 2005)
This paper summarizes findings from a formative research study conducted in Haiti to develop a behavior change communication (BCC) strategy to improve infant and child feeding practices and to reduce childhood malnutrition. It describes the methodology used and the tools developed to facilitate decisionmaking and effective use of formative research for program planning... The study used formative research methods that included individual and group interviews, food-rating exercises, and participatory recipe trials. The aims of the study were to (1) study current infant and young child feeding practices in the Central Plateau of Haiti, (2) identify individual, household, and community factors that may facilitate or constrain adoption of recommended behaviors, and (3) use the information from the formative research to prioritize behaviors and design an effective BCC strategy.